Completeness and validity of alcohol recording in general practice within the UK: a cross-sectional study - Mansfield,K; Crellin,E; Denholm,R; Quint,J; Smeeth,L; Cook,S; Herrett,E (BMJ Open, 2019)
Background: Since 2010 the National Institute for Health and Care Excellence has recommended screening adults for excessive alcohol consumption to try and help prevent alcohol-use disorders. Little is known about the extent to which these recommendations are followed, and the resulting completeness and validity of alcohol-related data recording in primary care. Objective: To investigate the completeness and accuracy of recording of alcohol use within primary care records in the UK.Design and setting: Cross-sectional study in the Clinical Practice Research DatalinkParticipants: We included all adult patients registered on 1st January 2018 with ≥1 year of follow-up. Primary and secondary outcome measures: We calculated prevalence of alcohol consumption recording overall and within patient groups. We then validated alcohol consumption data against recommended screening tools (AUDIT) as the gold standard. We also calculated how prevalence of alcohol recording changed over the preceding decade.Results: In 2018, among 1.8 million registered adult patients, just over half (51.9%) had a record for a code related to alcohol in the previous five years. Recording of alcohol consumption was more common among women, older people, ex-smokers, and those from more deprived areas, who were overweight/obese, or with comorbidities. A quarter of patients had units per week recorded in the last five years, but <10% had an AUDIT or FAST alcohol screening test score. The recorded alcohol measures corresponded to results from gold standard AUDIT scores. The distribution of consumption among current drinkers was similar to the Health Survey for England.Conclusions: Half of adults in UK primary care have no recorded alcohol consumption data. When consumption is recorded, we have demonstrated internal and external validity of the data, suggesting greater recording may help identify opportunities for interventions to reduce harms.